Evaluation of Enterprise Risk Management Implementation in Public Institutions Using Multidimensional Maturity Model - Permadi, Egi Agung; Hartanti, Dwi (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p12, 2025)
This study aims to evaluate the implementation of Enterprise Risk Management (ERM) at Institution X using a multidimensional maturity model. A case study approach with data collection through semi-structured interviews and internal document analysis. Content analysis is used to identify and evaluate the maturity level of each attribute according to the morphological matrix of the multidimensional model. The results of the study indicate that the ERM maturity level at Institution X is at Level 3 (Completed) on a scale of five. This level reflects that the organization has processed and continuously managed, identified, and assessed risks and formalized the risk management approach and clearly defined responsibilities. However, the Compliance and Strategy attributes still require more attention. Institution X needs to develop a professional strategy for risk management, improve the compliance management system, and use a multidimensional model for continuous evaluation in the future. These findings can be a basis for Institution X in formulating strategic steps to increase the level of ERM maturity. In addition, this study also contributes to the public sector as a reference in improving the quality of organizational risk governance. Keywords: Enterprise Risk Management; Multidimensional Model; Maturity Level; Risk Evaluation; Public Institutions